Efektivitas dan Efisiensi Pengelolaan Dana Bantuan Operasional Sekolah pada SMAN 2 Sidrap - Suci Febrianti (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study aims to describe the effectiveness and efficiency of the management of School Operational Assistance (BOS) funds at SMAN 2 Sidrap. BOS funds are a government program aimed at supporting the financing of school operational needs at the elementary and secondary education levels. This program is expected to improve access and quality of education, but its implementation is still faced with various obstacles such as delays in disbursement of funds, lack of transparency, and a suboptimal reporting system. This study uses a qualitative descriptive approach, with data collection techniques through in-depth interviews, field observations, and documentation studies. Informants in this study consisted of the principal, treasurer, teachers, and BOS fund management staff. The results of the study indicate that in general the management of BOS funds at SMAN 2 Sidrap has been running quite effectively and efficiently. Effectiveness is reflected in the use of funds that contribute to improving the quality of educational services, such as the procurement of learning facilities and the implementation of extracurricular programs. Efficiency is seen in the use of funds that refer to the priority scale of school needs. However, obstacles are still found such as delays in disbursement of funds from the central government that impact the smooth implementation of school activities, and financial reporting that has not been fully documented systematically and periodically. This research provides an important overview of the real conditions of BOS fund management in schools and is expected to provide input for related parties in order to improve the education financial governance system to make it more transparent, accountable, and sustainable.